Identités plurielles à l'école : catégorisations et diversité des pratiques - Stéphanie Galligani (Recherches en didactique des langues et des cultures)
This article focuses on the way education addresses the issue of the plural identities of children recently arrived in France to be schooled. Firstly, we will clarify what is meant by "identities" in the school context with a view to associating the notion with different categories used in official texts to identify foreign children. Whilst postulating the implication of the school as an institution in the (re)construction of the social identities of newcomers to France, the contextual parameters which influence plural identities and plurilingualism will be examined. We will base our arguments and reasoning on the initial results of a research project concerning a structure designed to welcome newcomers – a CRI (cours de rattrapage intégré), a special class focused on enabling these pupils to catch up and integrate normal classes – in a state primary school with international sections. This example will enable us to show how the "contextual culture" enables the education system to cater for plural identities and plurilingualism as an educational principle.